Prevalence and outcome of gestational diabetes mellitus in women from rural population attending antenatal clinic at a teaching hospital, Tamil Nadu, India - Muthuramalingam, Vidhya; Kumar, Amar Nagesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Prevalence of gestational diabetes mellitus shows wide variation across our country. From the recent studies, it is observed that incidence of gestational diabetes mellitus in antenatal women is increasing globally and India is not an exception from this. Gestational diabetes mellitus should be considered as a serious risk factor for both mother and baby as it affects two generations by having chance of developing diabetes and its related complications in future. Methods: A total of 585 pregnant women with 24 to 28 weeks of gestational age were recruited for the study. The study population was divided into four groups based on the age range; Group I include antenatal women with age <20 years, Group II includes antenatal women of age range 21-24 years, Group III includes antenatal women of age range 25-29 years, and Group IV includes antenatal women of age range ≥30 years. Results: In the present study GDM was diagnosed in 94 women among 585 antenatal women screened for GDM (16.06%). Majority of the studied population are in the age range of 20-29 years (441/585, 75.38%). The mean age of participants was 27.54±3.58 years (range 18-34 years). The prevalence of GDM was higher in the group of women aged ≥30 years (Group IV) followed by ≤20 years (Group I) (23.21% and 15.62% respectively) compared to the groups II and III (14.78% and 13.74% respectively). This observation was found to be statistically significant (p<0.001). Among 585 patients, delivery outcome was 100% successful, all delivered live babies, among them 64 patients delivered babies with macrosomia (11%). Conclusions: The study showed GDM prevalence of 16.06% from the neighboring rural villages attending our teaching hospital.